2021
DOI: 10.31234/osf.io/h3qy6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Status loss due to COVID-19, traditional masculinity, and the prediction of suicidal ideation and recent suicide attempts

Abstract: Background: The COVID-19 pandemic is causing extensive job loss leading to a loss of social status in many men. Endorsement of traditional masculinity ideology may render some men particularly sensitive to status loss and thereby to an increased risk for suicidality.Methods: In this anonymous online survey conducted in German-speaking European countries, 490 men completed questionnaires regarding loss of social status due to the pandemic, suicidal ideation and past-month suicide attempt. Furthermore, prototypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Positive associations between endorsement of TMI and higher externalizing depression, but not prototypical depression symptoms, were found only among heterosexual-identified men. Because stronger endorsement of TMI and high externalizing depression symptoms have been previously linked with suicidal ideation and suicide attempts among men (Coleman et al, 2020;Rice et al, 2018;Walther, Grub, Tsar, et al, 2021), these findings bear great clinical relevance as to recognize heterosexual-identified men with strong TMI and high externalizing symptoms as a highrisk group for intervention strategies and treatment policies.…”
Section: Discussionmentioning
confidence: 86%
“…Positive associations between endorsement of TMI and higher externalizing depression, but not prototypical depression symptoms, were found only among heterosexual-identified men. Because stronger endorsement of TMI and high externalizing depression symptoms have been previously linked with suicidal ideation and suicide attempts among men (Coleman et al, 2020;Rice et al, 2018;Walther, Grub, Tsar, et al, 2021), these findings bear great clinical relevance as to recognize heterosexual-identified men with strong TMI and high externalizing symptoms as a highrisk group for intervention strategies and treatment policies.…”
Section: Discussionmentioning
confidence: 86%
“…Men and women differ with regard to the prevalence of several mental disorders with women showing higher rates in depressive disorders, somatoform disorders, anxiety disorders, and eating disorders [ 1 , 2 , 3 , 4 , 5 , 6 ], while men show higher rates in substance use disorders and especially in alcohol use disorders [ 7 , 8 ]. Furthermore, men show up to four-fold increased suicide rates and appear to be particularly vulnerable to commit suicide when facing economic or social losses [ 9 , 10 ]. This is in line with reports suggesting that overall men and women experience similar levels of psychological distress and mental disorders [ 11 ], yet men use psychotherapy about 30% less than women [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Men's concern for passing COVID-19 to vulnerable others likely reflects normative protector traditions, where men are socialized to prioritize the welfare of others above their own (Courtenay, 2000). The finding that men were also commonly concerned about their own health regarding COVID-19 appears to contradict the narrative in past research that positions health risk behaviors as fundamental in demonstrating one's status as a "real" man (Levant & Wimer, 2014;Walther et al, 2021), where some men are identified as reticent to engage in preventive behaviors such as wearing masks and regular hand-washing (Mahalik et al, 2021), likely due to perceiving the pandemic as less serious relative to women (Gallasso et al, 2020). The message from the current data (i.e., that some men do see COVID as a realistic point of anxiety and are enacting measures to protect themselves and others), relative to the message from sex-differences research that tends to homogenize men as an unconcerned and careless group, reiterates the importance of withingender research to be able to understand which men are more or less likely to see COVID as a legitimate health risk and comply with protective public-health strategies.…”
Section: Impacts Of Covid-19 On Men's Mental Healthmentioning
confidence: 89%